The Effectiveness of Problem-Based Learning with Model Eliciting Activities Approach towards Problem Solving Competency - Candra Kusuma Nurjanah; Supandi Supandi; Agnita Siska Pramasdyahsari (Universitas PGRI Semarang, 2023)
The purpose of this study was to determine whether there was a difference in the average score and the effectiveness of problem based learning with the mathematics model eliciting activities approach to problem solving ability. The type of study is a quantitative research with a quasi experimental design using a pretest-posttest only control group design. The population in this study was class VIII SMPN 5 Jepara in the academic year 2022/2023 which consist of two classes. The sampling technique was carried out by purposive sampling technique, class VIII A was the control class and class VIII B was the experimental class. The data obtained through the pretest and posttest values were then processed by normality test, homogeneity test, T-Test, and N-Gain. The results obtained from the T-Test is a problem based learning model with an approach model of bringing up mathematical activities with a number of respondents 32 students and a mean of 81.22. While the control class taught by conventional learning has 31 students as respondents and the mean is 71.65. The value of t_count = 6.011 and a significance level of 5% obtained t_table = 1.999. Based on the t value, it can be written t_table (5% = 1.999) < t_count (6.011), then the results of the data analysis can be said that is rejected and is accepted so that